Microblogging in Educational Settings in College: Use of Twitter Beyond Teacher Assignments - Santiago Tejedor; Óscar Coromina; Gil Pla-Campas (Universidad Autónoma de Baja California, 2021)
The impact of Twitter can be strongly felt across a number of areas of professional and day-to-day life. By combining quantitative and qualitative methods, this article analyzes how young college students create content on Twitter in an academic setting, and how they perceive this content creation. To this end, a purposive sample of three groups of students was formed, a sample of 10,291 published tweets was collected, and a focus group was set up for each group of students. Among other findings, this study shows that students prioritize academic instructions and requirements and report that the way they use the platform depends on whether it is for an academic assignment or not.